The Role Of Patriotism In Shaping The Moral And Civic Values Of Youth - Xalilova, Zarnigor; Abdurahmonov, Husniddin; Mihmonaliyev, Hakimjon (TLEP – International Journal of Multidiscipline, 2025)
This article examines the role of patriotism in the upbringing of youth and its influence on the formation of moral and ethical maturity. It highlights the importance of education, family environment, mass media, and social organizations in fostering patriotism among the younger generation. The article also discusses the relevance of strengthening national pride and patriotic values in the context of globalization from a scientific perspective.